Fin Whale Sound Reception Mechanisms: Skull Vibration Enables Low-Frequency Hearing - Cranford, Ted W.; Krysl, Petr (PLOS ONE, 2015)
Hearing mechanisms in baleen whales (Mysticeti) are essentially unknown but their vocalization frequencies overlap with anthropogenic sound sources. Synthetic audiograms were generated for a fin whale by applying finite element modeling tools to X-ray computed tomography (CT) scans. We CT scanned the head of a small fin whale (Balaenoptera physalus) in a scanner designed for solid-fuel rocket motors. Our computer (finite element) modeling toolkit allowed us to visualize what occurs when sounds interact with the anatomic geometry of the whale’s head. Simulations reveal two mechanisms that excite both bony ear complexes, (1) the skull-vibration enabled bone conduction mechanism and (2) a pressure mechanism transmitted through soft tissues. Bone conduction is the predominant mechanism. The mass density of the bony ear complexes and their firmly embedded attachments to the skull are universal across the Mysticeti, suggesting that sound reception mechanisms are similar in all baleen whales. Interactions between incident sound waves and the skull cause deformations that induce motion in each bony ear complex, resulting in best hearing sensitivity for low-frequency sounds. This predominant low-frequency sensitivity has significant implications for assessing mysticete exposure levels to anthropogenic sounds. The din of man-made ocean noise has increased steadily over the past half century. Our results provide valuable data for U.S. regulatory agencies and concerned large-scale industrial users of the ocean environment. This study transforms our understanding of baleen whale hearing and provides a means to predict auditory sensitivity across a broad spectrum of sound frequencies.